(untitled) (Historia, 2021)
When asked to think about this, I realised that I was as much or more influenced by historians whose work I read than by those whom I encountered in my apprenticeship. In only a few cases were they the same people. Here I write mostly about those I met in person, rather than through their books. In my first year at UCT, I was most struck by Dave Nourse, who taught the History I survey course from the fall of Rome to the Second World War. He had the habit of opening his mouth like a fish before speaking, and the only words that I now remember coming out of his mouth were about the Sicilian Vespers. I liked the sweep of the course, and at the time was not critical of its Eurocentricity. I later learnt that Nourse owned a magnificent collection of Cromwelliana, which he bequeathed to what is now the National Library.